Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(x+y=3\)
\(\Rightarrow\)\(\left(x+y\right)^2=9\)
\(\Leftrightarrow\)\(x^2+y^2+2xy=9\)
\(\Leftrightarrow\)\(2xy=4\) do x2 + y2 = 5
\(\Leftrightarrow\)\(xy=2\)
\(x^3+y^3=\left(x+y\right)^3-3xy\left(x+y\right)=3^3-3.2.3=9\)
b) bạn làm tương tự
\(a,x+y=3\Rightarrow\left(x+y\right)^2=9\Rightarrow x^2+2xy+y^2=9\Rightarrow2xy=4\Leftrightarrow xy=2\)
Vì \(\left(x+y\right)=3\Rightarrow\left(x+y\right)^3=27\)
\(\Rightarrow x^3+3x^2y+3xy^2+y^3=27\)
\(\Rightarrow x^3+y^3+3xy\left(x+y\right)=27\)
\(\Rightarrow x^3+y^3+3.2.3=27\)
\(\Rightarrow x^3+y^3=27-18=9\)
\(b,x-y=5\Rightarrow\left(x-y\right)^2=25\Rightarrow x^2-2xy+y^2=25\Rightarrow2xy=-10\Leftrightarrow xy=-5\)
\(x^3-y^3=\left(x-y\right)\left(x^2+xy+y^2\right)=5.10=50\)
1,Thực hiện phép tính :
a, (x + 2)9 : (x + 2)6
=(x+2)9-6
=(x+2)3
b, (x - y) 4 : (x - 2)3
=(x-y)4-3
=x-y
c, ( x2+ 2x + 4)5 : (x2 + 2x + 4)
=(x2+2x+4)5-1
=(x2+2x+4)4
d, 2(x2 + 1)3 : 1/3(x2 + 1)
=(2÷1/3).[(x2+1)3÷(x2+1)]
=6(x2+1)2
e, 5 (x - y)5 : 5/6 (x - y)2
=(5÷5/6).[(x-y)5÷(x-y)2]
=6(x-y))3
Có: \(\left(x-y\right)^2=25\)
\(\Leftrightarrow-2xy=25-\left(x^2+y^2\right)=25-15=10\)
\(\Leftrightarrow xy=-5\)
\(x^3-y^3=\left(x-y\right)\left(x^2+xy+y^2\right)=5\cdot\left(15-5\right)=5\cdot10=50\)
x - y = 5
=>(x - y)2 = 25
=> x2 - 2xy + y2 = 25
=> 15 - 2xy = 25
=> 2xy = 15 - 25
=> 2xy = - 10
=> xy = -10 : 2
=> xy = -5
x3 - y3 = ( x - y ) ( x 2 - xy + y2)
=> x3- y3 = 5 . ( -5 . 15 )
= >x 3 - y 3 = - 375.
a: \(=\dfrac{5}{2}x-2x+\dfrac{7}{2}=\dfrac{1}{2}x+\dfrac{7}{2}\)
b: \(=\dfrac{-1}{4}x^4-3x^2+\dfrac{9}{4}x\)
c: \(=\dfrac{1}{5}x+\dfrac{1}{15}xy+\dfrac{7}{10}x^2\)
d: \(=-9x^3-1-12y+27xy\)
a,
\(x^2+y^2=\left(x+y\right)^2-2xy=1^2-2\cdot\left(-6\right)=1-\left(-12\right)=13\)
\(x^3+y^3=\left(x+y\right)\left(x^2-xy+y^2\right)=1\cdot\left[13-\left(-6\right)\right]=19\)
\(x^5+y^5=\left(x+y\right)\left(x^2+y^2\right)^2-\left(2x^3y^2+xy^4+x^4y+2x^2y^3\right)=169-\left[2\left(xy\right)^2\left(x+y\right)+xy\left(x^3+y^3\right)\right]=169-\left[2\cdot36\cdot1-6\cdot19\right]=211\)
Có: \(x-y=5\)
=>\(x^2-2xy+y^2=25\)
=>\(-2xy=25-\left(x^2+y^2\right)=25-15=10\)
=>\(xy=-5\)
\(x^3-y^3=\left(x-y\right)\left(x^2+xy+y^2\right)=5\left(15-5\right)=5\cdot10=50\)